Application of DInSAR for short period monitoring of initial subsidence due to longwall mining in the mountain west United States - Jessica M. Wempen (International Journal of Mining Science and Technology, 2020)
Differential Interferometric Synthetic Aperture Radar (DInSAR), a satellite-based remote sensing technique, has application for monitoring subsidence with high resolution over short periods. DInSAR uses radar images to measure centimeter-level surface displacements. In the images, ground resolution can be relatively high, with each data point (pixel) representing the average displacement over an area of several square meters. The image data are acquired regularly which allows subsidence to be monitored sequentially over short periods; imaging periods typically range from weeks to months. Monitoring subsidence over short periods with high spatial resolution has potential to provide insight into the dynamics of subsidence and into relationships between mine advance and subsidence. In this study, for three longwall mines in the western United States, initial subsidence occurring at the start of longwall advance is quantified over short periods (12–72 days). C-band interferometric wide swath Synthetic Aperture Radar (SAR) images from the Sentinel satellites are used to quantify the subsidence. Overall, the data show initial development of subsidence, expansion of the subsidence trough, and the advance of subsidence in the direction of mining. Keywords: Longwall mining, Interferometry, Subsidence